2005
DOI: 10.2337/diacare.28.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Drugs and Heart Failure Risk in Patients With Type 2 Diabetes in the U.K. Primary Care Setting

Abstract: OBJECTIVE -To assess the effects of antidiabetic drugs on the risk of heart failure in patients with type 2 diabetes.RESEARCH DESIGN AND METHODS -We conducted a retrospective cohort study with a newly diagnosed diabetes cohort of 25,690 patients registered in the U.K. General Practice Research Database, 1988 -1999. We categorized person-time drug exposures to monotherapies in insulin, sulfonylureas (SUs), metformins, and other oral hypoglycemic agents (i.e., acarbose, guar gum) and combination therapy includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 21 publications
(15 reference statements)
1
65
0
5
Order By: Relevance
“…First, we excluded patients with a history of insulin or thiazolidinedione use prior to cohort entry and censored patients upon receiving these medications during follow-up, given their reported association with an increased risk of CHF (15)(16)(17). Second, the use of metformin is not recommended in patients with renal insufficiency.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…First, we excluded patients with a history of insulin or thiazolidinedione use prior to cohort entry and censored patients upon receiving these medications during follow-up, given their reported association with an increased risk of CHF (15)(16)(17). Second, the use of metformin is not recommended in patients with renal insufficiency.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…One retrospective study indicated that this risk was associated with the severity and duration of diabetes and drug therapy [32]. Oral antidiabetic agents probably increase the risk of cardiovascular events.…”
Section: Discussionmentioning
confidence: 97%
“…Фактор влияния антидиабетической терапии и динамики гликемии, со-гласно результатам анализа исследовательской базы дан-ных Великобритании, показал, что применение любой антидиабетической терапии ассоциировано с повыше-нием частоты СН на краткосрочной основе. От момента инициации терапии динамика показателей отношения рисков (OP) составляет 4,75 (95% ДИ 3,57-6,33) в те-чение первого года от момента назначения антидиабе-тической терапии, далее 1,21 (0,82-1,78) и снижается до 0,89 (0,70-1,14) в последующий период наблюде-ния [15]. С одной стороны, это может быть связано с большей частотой назначения лекарственной терапии пациентам с СН, но нельзя исключить и то, что сниже-ние гликемии у этих пациентов, возможно, приводит к усугублению состоя ния миокарда и прогрессированию СН [15].…”
Section: влияние контроля гликемии на частоту развития сер-дечной недunclassified
“…От момента инициации терапии динамика показателей отношения рисков (OP) составляет 4,75 (95% ДИ 3,57-6,33) в те-чение первого года от момента назначения антидиабе-тической терапии, далее 1,21 (0,82-1,78) и снижается до 0,89 (0,70-1,14) в последующий период наблюде-ния [15]. С одной стороны, это может быть связано с большей частотой назначения лекарственной терапии пациентам с СН, но нельзя исключить и то, что сниже-ние гликемии у этих пациентов, возможно, приводит к усугублению состоя ния миокарда и прогрессированию СН [15]. Интересная параллель может быть проведена с ранним и преходящим ухудшением состояния глаз-ного дна у пациентов с СД 1 типа в группе интенсив-ного контроля, отмеченным в исследованиях The Kroc Collaborative Study и DCCT [16,17].…”
Section: влияние контроля гликемии на частоту развития сер-дечной недunclassified